Cooperative and networking strategies in small business - Peris-Ortiz, Marta; Ferreira, João J. M. (Springer, 2017)
The book aims to collect the most recent research and best practices in the cooperative and networking small business field identifying new theoretical models and describing the relationship between cooperation and networks in the small business strategy context. It examines different concepts and analytical techniques better understand the links between cooperative strategies and networks in small business. It also studies the existing economic conditions of network and strategic implications to small business from the point of view of their internal and external consistency. Cooperation and networks is a fashionable topic. It is receiving increasing attention in popular management publications, as well as specialized academic journals. Cooperation between firms and industries is a means of leveraging and aggregating knowledge also generating direct benefits in terms of innovation, productivity and competitiveness. Various options and decisions made within the framework of strategic alliances may be identified and differentiated. For example, it has been argued that R & D cooperation between competing firms also facilitates the search for incremental efficiency gains and is thus a competitive advantage. In parallel with a theoretical acceptance of the importance of a sustained competitive advantage to formulate strategy, there is a growing understanding that cooperative and networking behavior among small firms is at the root of many success stories in today's small business management. This condition requires an effort to develop a study of both aspects of cooperation and networks as compatible, complementary facets of a unique reality. In short, the cooperative and networking relationships of a small business can be the source of its competitive advantage. Enhancement of local resources and capabilities for the generation and dissemination of knowledge is still an issue for defining public policies in many countries. Featuring contributions covering such topics as green innovation, social commerce, university cooperation networks, and regional entrepreneurship, this book provides a comprehensive and richly illustrated study of cooperation and networks in small business that will be pertinent to students, academics, professionals, scholars, and policy makers.
Keywords: Small business -- Management.; Strategic alliances (Business); Business networks.; Cooperation.; elektronické knihy; electronic books